Réponses

2014-09-11T00:39:24+02:00
Bonsoir

a) x² - 6x + 9

identifiant a, b et c
a = 1, b = -6 et c = 9
calculons Δ

Δ = b² - 4ac
Δ = (-6)² - 4(1)(9) = 36 - 36 = 0

x² - 6x + 9
la forme canonique est
(x-3)²

b) 2x² + x + 1
a = 2 b = 1 et c = 1
Calculons Δ
Δ = (1)² - 4(2)(1) = 1 - 8 = -7

Forme canonique
2[(x+1/4)² + 7/16]

c) -3x² + x
a = -3, b = 1 et c = 0
Δ = (1)² - 4(-3)(0) = 1

Forme canonique
-3[(x-1/6)² - 1/36]

d) 2x² - 4x√2 - 7
a = 2, b = 4√2 et c = -7

Δ = (-4√2)² - 4(2)(-7)
Δ = 32 + 56
Δ = 88

Forme canonique
2[(x-√2)² - 88/16]